Graves’ disease: A review in diagnosis and management - I Gusti Ngurah Bagus Hindra Dwisaputra; I Made Yoga Prabawa (Intisari Sains Medis, 2020)
Background: Graves’ disease is the leading cause of hyperthyroidism condition in the world. The incidence of Graves’ disease in the world reaches 20-50 cases per 100,000 population per year. Graves’ disease can cause somatic, psychiatric, and cosmetic problems in the patient. In some cases, it caused a decreased quality of life and death if not appropriately managed. Hence, appropriate diagnosis and management should be made to prevent the progression of the disease.Aim: This literature review aims to review the diagnosis and management of Graves’ disease.Conclusion: Graves’ disease is an autoimmune disease that causes hyperthyroidism by stimulating the thyroid gland to produce thyroid hormone. History taking and laboratory investigation can be done to establish a diagnose of Graves’ disease. Treatment, including the use of anti-thyroid drugs, radioiodine therapy, and surgery. Monitoring should be done periodically during and after the course of treatment to prevent relapse.